PHYSIOLOGICAL AND MOLECULAR CHARACTERIZATION OF Ascochyta rabiei ISOLATES FROM VARIOUS CHICKPEA AREAS ACROSS IKR, IRAQ - Al-Maaroof, Emad M.; M. Salih, Rezan (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
From 2017 to 2019, 51 A. rabiei isolates were isolated from 259 chickpea fields across IKR. On different media, 32 isolates showed significant differences in morphological characteristics. The isolates were divided into six groups based on colony color, five groups on mycelium color and three groups on pycnidia color. CSMDA was the best media for mycelial growth. AS-28 significantly surpassed all other isolates in colony diameter despite media type. A. rabiei growth varied between 15-35°C, the maximum growth occured at 25°C and ceased at 35°C. The mean conidia and pycnedia dimensions in isolates AS-19 and AS-9 ranged from 20.0*7.5μm and 70.8*47.9μm to 21.8*9.0μm and 140.7*93.6μm in AS-11 and AS-18 respectively. The isolates were classified into four groups and 15 races based on pathogenicity and virulence. Race 1 exhibited high aggressiveness and virulence against all differentials, whereas the other races explored variable virulence spectrum. Sulaimani had the greatest A. rabiei diversity, with nine different races accounting for 60% of population, followed by Erbil with five races (33%). Halabja and Garmian each contribute three and two races, accounting for 20% and 12% of the total. Races 4 and 5 were the most populous and widely spread in IKR. The ITS region was amplified to a541bp band in all A. rabiei isolates. The length of the nucleotide sequences ranged from 481 to 541bp. The ITS sequences of all the isolates were registered at the NCBI Gen Bank under different accession numbers. The phylogenetic tree clearly shows that all the isolates are grouped in one cluster and have a high degree of similarity.